2010
DOI: 10.1017/s1551929510000957
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy Imaging of Living Cells

Abstract: Over the last two decades, Atomic Force Microscopy (AFM) has emerged as the tool of choice to image living organisms in a near-physiological environment. Whereas fluorescence microscopy techniques allow labeling and tracking of components inside cells and the observation of dynamic processes, AFM is mainly a surface technique that can be operated on a wide range of substrates including biological samples. AFM enables extraction of topographical, mechanical and chemical information from these samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…Thus, we used PBP4 mutants to test whether highly cross-linked peptidoglycan was required for increased mechanical resistance of live S. aureus cells. For this purpose, we used AFM in PeakForce QNM, a method that detects material variations (such as elasticity or adhesion) at high resolution across a simultaneously acquired topographic image (35)(36)(37). To access primarily the cell wall properties, we used experimental conditions in which the cantilever indentation was less than the proposed thickness of the cell wall, which is in the range of 35 nm (9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we used PBP4 mutants to test whether highly cross-linked peptidoglycan was required for increased mechanical resistance of live S. aureus cells. For this purpose, we used AFM in PeakForce QNM, a method that detects material variations (such as elasticity or adhesion) at high resolution across a simultaneously acquired topographic image (35)(36)(37). To access primarily the cell wall properties, we used experimental conditions in which the cantilever indentation was less than the proposed thickness of the cell wall, which is in the range of 35 nm (9).…”
Section: Resultsmentioning
confidence: 99%
“…A silicone cover was used to create a hydrophobic area around the filter, which was then filled with 1:10 TSB/PBS solution. AFM measurements were performed in the TSB/PBS solution at room temperature using a Bioscope Catalyst (Bruker) in PeakForce QNM (Bruker) mode (36,37). The bacterial samples were freshly prepared for each series of measurements and characterized usually within 30 min and never later than 2 h after harvesting.…”
Section: Afm Elasticity Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, AFM based force spectroscopy is increasingly used to study the mechanisms of molecular recognition and protein folding/unfolding, to probe chemical groups and dynamics of receptor-ligand interactions (Florin et al 1994;Dorobantu and Gray, 2010;Rico et al, 2011), and to study the local elasticity (Clausen-Schaumann et al, 2000) and the mechanical properties of soft biological samples (Butt et al, 2005;Müller and Dufrene, 2008). The AFM has also provided nanometer-scale resolution imaging of biological samples ranging from single molecules, such as DNA (Hamon et al, 2007), to intact cells attached on biomaterials (Berquand et al, 2010). Emerging applications include increasing the resolution of mechanical measurements in biological contexts such as cell division (Gilbert et al, 2007;Stewart et al, 2011) or cell adhesion (Li et al, 2003;Fierro et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, such measurements can be performed seamlessly in physiological conditions and in presence of different liquid media. This versatility is reflected in the AFM literature which presents with increasing frequency novel results regarding mechanical properties of single cells, bacteria or even single molecules (Berquand et al, 2010;Kasas and Dietler, 2008). At a cellular scale, it has been demonstrated that the mechanical properties of the membrane can reflect the physiological state of the entire system and that these properties are clearly altered in the occurrence of pathological conditions (Cross et al, 2007;Girasole et al, 2010;Lekka et al, 2005).…”
Section: Introductionmentioning
confidence: 99%